Review of orthopaedic trauma - Brinker, Mark R. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"The second edition of Review of Orthopaedic Trauma covers the entire scope of adult and pediatric trauma care. Emphasis is placed on material likely to appear on board and training exams. An easy-to-use outline is provided for rapid access, exam preparation, or review of new and emerging topics. Information is organized by anatomic region"--Provided by publisher